Spatial Assessment of Drinking Water Quality in Mardan City, Khyber Pakhtunkhwa, Pakistan - Muhammad Ibrahim; Ihsanullah; Ghani Rahman; Muhammad Hamza (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
The quality water is needed for human health. However, most of the water supply agencies focus on only water supply aspect instead of water quality. Majority of the consumers are also not aware of the importance of water quality. In the present study, samples of drinking water were collected from households located in Mardan city. These water samples were evaluated for physical parameters (electrical conductivity (EC), pH, total hardness, total dissolved solids (TDS), and turbidity) and chemical parameters (sulphates, nitrates, sodium, chlorides and potassium ions). The physical parameters (pH, alkalinity, total hardness and TDS) and chemical parameters (sodium, chloride and nitrate) in all the water samples were found according to the guidelines prescribed by WHO for the quality of drinking water. However, this study has shown abnormal conditions regarding physical parameters (turbidity 0.82 NTU and EC 1480 μS/cm) and chemical parameters (potassium 13.7 mg/l and sulphates 512 mg/l) at selected sample areas. These water samples values are higher than the guidelines values recommended by WHO for the quality of drinking water. Therefore, it can be concluded that the groundwater quality at the majority places are safe drinking purposes in the study area.